How usable are capital buffers? An empirical analysis of the interaction between capital buffers and the leverage ratio since 2016 - Georg Leitner; Michal Dvoérák; Alessandro Magi; Balázs Zsámboki (European Central Bank (ECB), 2023)
This paper analyses banks' ability to use capital buffers in the euro area, taking into account overlapping capital requirements between the risk-based capital framework and the leverage ratio capital framework from 2016 to 2022. This analysis is the first to quantify buffer usability in multiple jurisdictions and across various bank types, identify key drivers of buffer usability and assess the impact of various policy measures using longer time series. The paper shows that while both risk-based and leverage frameworks play a key role in enhancing the resilience of the banking system and ensuring financial stability, their simultaneous application creates interactions that may affect the functioning of capital buffers. In this regard, we investigate to what extent banks could have drawn down regulatory capital buffers in the risk-based framework without breaching current leverage ratio requirements, which is in line with the approach to buffer usability taken in ESRB (2021b). We show that buffer usability was partially constrained in the period examined and is expected to remain so under the current regulatory framework and if risk weight densities (RWDs) remain low. This finding indicates that the leverage ratio constitutes an effective backstop to the risk-based framework, both as regards minimum requirements and capital buffers. Limited buffer usability was identified especially for global systemically important institutions (G-SIIs) that rely largely on internal modelling approaches to calculate risk-based capital requirements, leading to comparably low risk weights and making the leverage ratio relatively more binding. Adding to previous contributions, we find that banks' ability to use capital buffers fluctuated over time, generally increasing before 2019 and decreasing after the start of the coronavirus (COVID-19) pandemic, with substantial heterogeneity across countries. Furthermore, we provide new insights into the relationship between the RWD of a bank and its buffer usability and find that there is a critical RWD range between 25% and 50% for which buffer usability is limited and very sensitive to RWD changes. Additionally, we perform a counterfactual analysis that investigates how a positive neutral countercyclical capital buffer and leverage ratio buffers would have changed buffer usability over time. Finally, we assess the impact of the implementation of the new Basel capital standards (Basel III) and find that full implementation of Basel III will materially increase the usability of capital buffers for G-SIIs.
Keywords: G21; G28; 330; macroprudential policy; capital buffers; buffer usability; bankingregulation; leverage ratio